Who took my strawberries?: a book about learning to share (Educational Technologies Ltd Place of publication not identified, 2004)
"Who Took My Strawberries?: A Book About Learning to Share" is a delightful story about a little rabbit named Rosie who discovers that her freshly picked strawberries have disappeared. At first, Rosie feels upset and refuses to share any more of her fruit. However, as she searches for the culprit, she realizes that sharing with her woodland friends brings more joy than keeping everything to herself. Through her journey, Rosie learns the value of generosity and how sharing can create happiness for everyone. The story gently teaches children the importance of sharing and building friendships through kindness.